Low-Cost “Telesimulation” Training Improves Real Patient Pediatric Shock Outcomes in India - James, Ebor Jacob G.; Vyasam, Siva; Venkatachalam, Shakthi; Sanseau, Elizabeth; Cassidy, Kyle; Ramachandra, Geethanjali; Rebekah, Grace; Adhikari, Debasis D.; Deutsch, Ellen; Nishisaki, Akira; Nadkarni, Vinay M. (Frontiers in Pediatrics, 2022)
Abstract Introduction: Pediatric shock, especially septic shock, is a significant healthcare burden in low-income countries. Early recognition and management of shock in children improves patient outcome. Simulation-based Education (SBE) for shock recognition and prompt management prepares interdisciplinary pediatric emergency teams (PET) in crisis management. COVID-19 pandemic restrictions to in-person simulation led us to the development of telesimulation. We hypothesized that telesimulation training would improve pediatric shock recognition, process of care and patient outcomes in both simulated and real patient settings. Methods: We conducted a prospective quasi-experimental interrupted time series cohort study over nine months. We conducted 40 telesimulation sessions for 76 participants in teams of 3 or 4 utilizing the video telecommunication platform (Zoom©). Trained observers recorded time critical interventions on real patients for the PET composed of residents, fellows and nurses. Data were collected on 332 pediatric patients in shock (72% septic shock) before, during, and after the intervention. The data included the first hour time-critical intervention checklist, patient hemodynamic status at the end of first hour, time to resolution of shock and team leadership skills in the emergency room. Results: There was a significant improvement in the percent completion of tasks by the PET in simulated scenarios (69% in scenario 1 vs 93% in scenario 2; p<0.001). In real patients’ completion of tasks as per time-critical steps reached 100% during and post-intervention compared to the pre-intervention phase (87.5%), p<0.05. Significant improvement in the first hour hemodynamic parameters of shock patients: pre (71%), during (79%) and post (87%) intervention. (p<0.007 pre vs post) was noted. Shock reversal time reduced from 24 hours pre-intervention to 6 hours intervention and to 4.5 hours post-intervention (p<0.002). There was also a remarkable improvement in leadership performance assessed by Concise Assessment of Leader Management (CALM) instrument during the simulated (p<0.001) and real patent care in post-intervention (p<0.05). Conclusion: Telesimulation training is feasible and improved the process of care, time-critical interventions, leadership in both simulated and real patients and resolution of shock in real patients. To our knowledge, this is one of the first studies where telesimulation has shown improvement in real patient outcomes.